Pemanfaatan Media Sosial Oleh Penyuluh Pertanian Di Kecamatan Tomohon Tengah Kota Tomohon - Sinaga, Ina Geno Veva; Memah, Melsje Yellie; Pangemanan, Paulus Adrian (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
The aim of this research is to describe the use of social media by agricultural instructors in BPP Central Tomohon sub-district. The research took place from April to June 2024. The data collected was primary data obtained by direct interviews with extension workers in Central Tomohon District using a questionnaire. Secondary data was taken from BPS Tomohon City as well as research reports, journals and from the internet related to this research. The full sample used was all the instructors in the Extension Agency in Central Tomohon District, namely 10 people. The results of this research show that the use of social media by extension workers in Tomohon Tengah District, Tomohon City, uses social media which is classified as frequent, namely the use of social media Facebook, WhatsApp and YouTobe. The use of Instagram social media is classified as infrequent and non-use category. Almost all instructors access social media, be it Facebook, WhatsApp, Instagram or YouTube. The average use of social media by agricultural instructors is less than 2 hours